Hadith #1714 - Sahih al-Bukhari - Hammam (Sahih al-Bukhari)
The Prophet (ﷺ) performed four `Umra (three) in Dhi-l-Qa’da except the (one) `Umra which he performed with his Hajj: His `Umra from Al-hudaibiya, and the one of the following year, and the one from Al- Jr’rana where he distributed the booty (of the battle) of Hunain, and another `Umra with his Hajj.
Grade: Sahih

Hadith #1863 - Sahih al-Bukhari - Hammam (Sahih al-Bukhari)
I saw `Uthman performing ablution; he washed his hands thrice, rinsed his mouth and then washed his nose, by putting water in it and then blowing it out, and washed his face thrice, and then washed his right forearm up to the elbow thrice, and then the left-forearm up to the elbow thrice, then smeared his head with water, washed his right foot thrice, and then his left foot thrice and said, “I saw Allah’s Apostle performing ablution similar to my present ablution, and then he said, ‘Whoeve
Grade: Sahih

Hadith #6841 - Sahih al-Bukhari - Hammam (Sahih al-Bukhari)
(Usama’s Maula) Usama (bin Zaid) sent me to `Ali (at Kufa) and said, “`Ali will ask you, ‘What has prevented your companion from joining me?’ You then should say to him, ‘If you (`Ali) were in the mouth of a lion, I would like to be with you, but in this matter I won’t take any part.’ ” Harmala added: “`Ali didn’t give me anything (when I conveyed the message to him) so I went to Hasan, Hussain and Ibn Ja`far and they loaded my camels with much (wealth).
Grade: Sahih

Hadith #7006 - Sahih al-Bukhari - Hammam (Sahih al-Bukhari)
Hudhaifa said, “O the Group of Al-Qurra! Follow the straight path, for then you have taken a great lead (and will be the leaders), but if you divert right or left, then you will go astray far away.”
Grade: Sahih